Left atrial appendage clipping as an adjunctive therapy in lung cancer surgery for patients with atrial fibrillation: a case report. Issue 1 (10th January 2020) - Toale, Conor; Jones, John; Fitzmaurice, Gerard J; Eaton, Donna
Abstract: The left atrial appendage (LAA) is thought to be responsible for the vast majority of embolic strokes, and has become an important target in the surgical management of atrial fibrillation (AF). Epicardial clipping of the LAA has emerged as a potentially safe, durable and effective method of surgical closure, and has been performed both as a stand-alone procedure (thoracoscopic LAA clipping) and as an adjunct in patients undergoing open cardiac surgery. To our knowledge, the use of epicardial clipping in the setting of non-cardiac thoracic surgery for patients with concurrent diagnosis of AF has not been previously reported. This report highlights the case of a 70-year-old gentleman with a diagnosis of AF, who underwent concomitant LAA clipping at the time of elective thoracoscopic left upper lobectomy for a pT2aN0 lung adenocarcinoma. To our knowledge, this is the first report demonstrating the feasibility of LAA clipping as an adjunctive procedure in lung cancer surgery.